1986
DOI: 10.1159/000260920
|View full text |Cite
|
Sign up to set email alerts
|

On the Properties of Fluoride Solutions Used for Topical Treatment and Mouth Rinse

Abstract: A number of solutions used for topical application and mouth rinsing were analyzed and calcium fluoride formation on human enamel at 20 °C determined. In most solutions free fluoride and hydrogen fluoride were the main ion species, whereas stannous hydroxide and stannous fluoride ion pairs were the dominating components of stannous fluoride solutions. The calcium fluoride formation on enamel was assessed by chemical analysis. It was found that an increase in fluoride activity and a decrease in pH increased the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
13
0

Year Published

1988
1988
2015
2015

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 14 publications
1
13
0
Order By: Relevance
“…In previous studies we have found that the yield of calcium fluoride from a neutral 2% sodium fluoride solution ranges around 0.1-1 nmol calcium fluoride material per square millimeter of enamel surface [Larsen and Jensen, 1986;Larsen and Richards, 1998]. Although direct comparison between studies must be cautious, similar results have been obtained by other workers [Saxegaard and Rølla, 1988;Bruun and Givskov, 1991].…”
supporting
confidence: 59%
“…In previous studies we have found that the yield of calcium fluoride from a neutral 2% sodium fluoride solution ranges around 0.1-1 nmol calcium fluoride material per square millimeter of enamel surface [Larsen and Jensen, 1986;Larsen and Richards, 1998]. Although direct comparison between studies must be cautious, similar results have been obtained by other workers [Saxegaard and Rølla, 1988;Bruun and Givskov, 1991].…”
supporting
confidence: 59%
“…Further, in previous studies we found that topical treatment of a tooth with neutral 2% NaF yields up to 0.5 nmol CaF 2 /mm 2 enamel surface. For a large tooth with a surface area of 500 mm 2 , this corresponds to a total of 0.25 Ìmol calcium fluoride [Larsen and Jensen, 1986;Larsen and Richards, 2001]. In comparison, this study showed that 1 litre of prepared fruit drink may dissolve from 0.31/2 = 0.15 mmol calcium fluoride (Rynkeby) to 0.99/2 = 0.5 mmol (Fun Rhubarbs, table 1) calcium fluoride, which is 150-500 Ìmol calcium fluoride, equivalent to what can be deposited at the surface of 600-2,000 teeth.…”
Section: Discussionmentioning
confidence: 99%
“…CaF 2 interferes with de-and remineralization processes during acid attacks by elevating fluoride levels through slow dissolution (1)(2)(3). The amount of CaF 2 formed is known to depend on several factors, such as fluoride concentration, the time of exposure, the pH of the solution, phosphate and salivary calcium concentration (4)(5)(6)(7)(8)(9). The availability of calcium ions is an important factor for calcium fluoride formation (7).…”
Section: Introductionmentioning
confidence: 99%